Error Analysis Of Countable And Uncountable Nouns In Writing Descriptive Text At First Grade - Hutasoit, Jona; Lestari, Febrika Dwi; Sitorus, Nurhayati (Jurnal Ilmu Pendidikan dan Sosial, 2026)
This study aims to examine the types and frequency of students’ errors in using countable and uncountable nouns in descriptive text writing. The research was conducted at SMK IT Insan Kreatif Tanjung Morawa, focusing on first-grade students. The objectives of the study are: (1) to identify the types of grammatical errors made by students in applying countable and uncountable nouns, and (2) to determine the most dominant type of error. This research employed a descriptive qualitative method, and the participants consisted of 28 students from class X-A. The data were obtained from students’ written descriptive texts, which were then analyzed based on the Surface Strategy Taxonomy by Dulay, Burt, and Krashen (1982). The analysis revealed that four main types of errors occurred: omission (41.46%), misordering (24.39%), addition (21.95%), and misformation (12.19%). Among these, omission errors were the most dominant. These errors occurred due to several factors, including a lack of understanding of noun classification rules, limited vocabulary, and insufficient exposure to correct usage in context. Additionally, many students confused uncountable nouns with plural countable nouns, resulting in inappropriate use of determiners and verb forms. The findings of this study suggest that English teachers need to emphasize targeted instruction on countable and uncountable nouns, integrate corrective feedback, and provide contextualized practice to help students internalize correct grammatical structures. This research also contributes to the broader field of English language teaching by offering insights into common learner difficulties in grammar, which can be addressed through enhanced pedagogical strategies